Treatment of Poor Sperm Quality and Erectile Dysfunction With Oral Pentoxifylline: A Systematic Review - Lu, Yi; Su, Hao; Zhang, Jianzhong; Wang, Yutao; Li, Hongjun (Frontiers in Pharmacology, 2022)
Background: Pentoxifylline (PTX) is a member of methylxanthine chemicals and a type of non-selective phosphodiesterase-5 inhibitors, which has been used in male infertility treatment to improve sperm quality and erectile dysfunction (ED) treatment. Mutually tight associations existed between ED and male infertility. Using PTX might kill two birds with one stone by improving sperm quality and erectile function in infertile men with ED. Methods: PubMed, Cochrane Library, EMBASE, and Web of Science were searched by October 2021. Based on available evidence from observational studies and randomized-controlled trials (RCTs), we conducted a systematic review to summarize the efficacy and safety of PTX in treating ED and male infertility. The protocol of the article was registered and updated in PROSPERO (CRD42021291396). Results: From 202 records, eight studies (7 RCTs) evaluating the role of PTX in ED and three studies (2 RCTs) assessing the efficacy of PTX in male infertility were included in the systematic review. Three studies (100.00%) and two studies (100.00%) reported the beneficial role of PTX in improving sperm progressive motility and normal sperm morphology rate, respectively. In contrast, only one study (33.33%) indicated the favorable role of PTX in enhancing sperm concentration. As for ED, three (60.00%) studies supported the treatment role of PTX alone in ED, and two studies (66.67%) favored the combination use of PTX and selective PDE5Is compared with selective PDE5Is alone. Safety analysis showed that PTX was a well-tolerated drug in ED and male infertility treatment. Conclusion: Given the association between ED and male infertility and satisfying findings from available evidence, PTX administration for the simultaneous treatment of poor sperm quality and mild ED in infertile men will highly enhance the treatment compliance. However, the finding should be treated carefully until validated by further studies.